2020
DOI: 10.1002/jgm.3260
|View full text |Cite
|
Sign up to set email alerts
|

Association of strong risk of hTERT gene polymorphic variants to malignant glioma and its prognostic implications with respect to different histological types and survival of glioma cases

Abstract: Background: Germline genetic variants of human telomerase reverse transcriptase (hTERT) are known to predispose for various malignancies, including glioma. The present study investigated genetic variation of hTERT T/G (rs2736100) and hTERT G/A (rs2736098) with respect to glioma risk. Methods: Confirmed cases (n = 106) were tested against 210 cancer-free healthy controls by the polymerase chain reaction-restriction fragment length polymorphism technique for genotyping. Results: Homozygous variant 'GG' genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“… 46 Similarly, an Indian study reported that rs2736100 contributes to a poorer prognosis of glioma patients. 47 On the other hand, a Chinese study did not seem to validate the relationship between this polymorphism and a poor prognosis in papillary thyroid carcinoma. 48 It is essential to consider that the mentioned studies did not focus on MM and were not conducted on Caucasians, thus caution should be applied when interpreting the data.…”
Section: Discussionmentioning
confidence: 95%
“… 46 Similarly, an Indian study reported that rs2736100 contributes to a poorer prognosis of glioma patients. 47 On the other hand, a Chinese study did not seem to validate the relationship between this polymorphism and a poor prognosis in papillary thyroid carcinoma. 48 It is essential to consider that the mentioned studies did not focus on MM and were not conducted on Caucasians, thus caution should be applied when interpreting the data.…”
Section: Discussionmentioning
confidence: 95%
“…TERT occurs widely in a variety of malignant tumors, is related to the prognosis of patients, 7 and is highly expressed in glioma tissues. 8 In this study, the gene mutation of IDH1/2 and TERT promoter region was sequenced, and the postoperative follow-up was carried out. The relationship between the gene mutation and the occurrence, development and prognosis of glioma, was examined to provide a theoretical basis, and possible therapeutic target, for the treatment of glioma.…”
Section: Introductionmentioning
confidence: 99%